Systemic Epstein–Barr Virus-Positive T/NK Lymphoproliferative Diseases With SH2D1A/XIAP Hypomorphic Gene Variants - Ishimura, Masataka; Eguchi, Katsuhide; Shiraishi, Akira; Sonoda, Motoshi; Azuma, Yoshihiro; Yamamoto, Hiroyuki; Imadome, Ken-ichi; Ohga, Shouichi (Frontiers in Pediatrics, 2019)
X-linked lymphoproliferative disease (XLP) is one of the X-linked primary immunodeficiency diseases (PIDs) reportedly to have a defective immune response to Epstein-Barr virus (EBV) infection. Mutations in SH2D1A and XIAP genes cause XLP. Systemic EBV-positive T-cell and natural killer (NK)-cell lymphoproliferative diseases (LPD) consist of the 3 major types; EBV-positive hemophagocytic lymphohistiocytosis (HLH), chronic active EBV infection (CAEBV), and EBV-positive T-cell/NK-cell lymphoma. CAEBV is recognized as a poor prognostic disease of EBV-associated T-cell and NK-cell LPD arising from the clonal proliferations of EBV-infected T cells (CD4+, CD8+, TCRγδ+) and/or NK cells. The majority of cases with CAEBV were reported from East Asia and South America. In Caucasian patients with chronic active EBV disease, the target of infection is exclusively B cells. These imply a genetic predisposition to EBV-positive T/NK cell LPD according to the ethnicity. In reported cases with XLP, EBV-infected cells are B cells. On the other hand, no mutation of SH2D1A/XIAP genes have been determined in patients with T/NK cell type (Asian type) CAEBV. We here describe, for a first time, four case-series of CAEBV/EBV-HLH patients who carried the hypomorphic variants of XLP-related genes. These cases included a male patient with CAEBV carrying SH2D1A hypomorphic mutation (c.7G>T, p.Ala3Ser) and two male patients with CAEBV/EBV-HLH carrying XIAP hypomorphic variant (c.1045_1047delGAG, p.Glu349del), along with the other female patient with CAEBV carrying the same XIAP variant. The female case underwent a bone marrow transplantation from a healthy HLA-matched sister having the same XIAP variant. Although a compete donor chimerism was achieved with the resolution of laryngeal LPD lesions, systemic donor-derived CD4+ T cell EBV-LPD developed during the control phase of intractable graft-versus-host-disease. These observations demonstrated that SH2D1A and XIAP genes are critical for the complete regulation of systemic EBV-positive T/NK cell LPD.